Incidence and Predictors of Radiation Retinopathy after I125 Plaque Brachytherapy for the Treatment of Choroidal Melanoma - Neves, Emmanuel (2023)
INTRODUCTION: Plaque brachytherapy is an established modality for the treatment of eligible choroidal melanomas. Radiation retinopathy (RR) is a known complication of brachy- therapy, responsible in part for the loss of vision after treatment. We aim to present the first report on the incidence and the predictors of radiation retinopathy after the treatment of choroidal mela- nomas in the Portuguese Ocular Oncology Reference Centre. METHODS: Retrospective case series of eligible choroidal melanoma patients submitted to plaque brachytherapy with I125 in the Ocular Oncology Unit of the Coimbra University and Hos- pital Centre (CHUC) between 2013-2021. Clinical, tumor and treatment variables were collected. Primary endpoints were defined as the cumulative incidence and the incidence rate of RR. Sec- ondary endpoints were the clinical predictors of RR as obtained through multivariable logistic regression. Candidate variables were determined through univariate logistic regression, based on clinical and an α level of 0.15. Using these variables, we built a stepwise multivariable logistic regression model, for which we considered an α level of 0.05. RESULTS: We included 150 eyes of 150 patients, mean aged 61.1±13.3 years and a median follow-up time of 33.5 months (15-52). Incidence rate of RR was 2.14/100 person-years, and the cu- mulative incidence of radiation retinopathy was 44.7% (67/150). Median time to RR development was 13 (7-18) months. Multivariable logistic regression revealed increased odds of RR with higher baseline tumor thickness (OR 1.39; 1.17-1.65; p<0.01), decreased odds of RR with pre-equator lo- cation of the tumor (OR 0.32; 0.11-0.95; p=0.04), and a trend towards decreased odds of RR with increasing age (OR 0.97; 0.95-1.00; p=0.07). CONCLUSION: The incidence of radiation retinopathy in our cohort agrees with results of published landmark trials in plaque brachytherapy. Increased baseline tumor thickness increased the odds of RR, while pre-equatorial location protected against RR and increased age showed a trend towards a protective effect.